1985
DOI: 10.2134/agronj1985.00021962007700010026x
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer Effects on Crop Removal of P and K in ‘Coastal’ Bermudagrass Forage1

Abstract: In 1959, an N‐P‐K ratio of 9.1‐1‐3.8 (4‐1‐2 N‐P2O5‐K2O ratio) was proposed as the proper nutrient balance for fertilizing ‘Coastal’ bermudagrass [Cynodon dactylon (L.) Pers.] for forage, but nutrient removal in forage was not taken into consideration with this ratio. The purpose of the study was to determine fertilizer effects on removal of P and K in ‘Coastal’ bermudagrass forage using increments of a fixed N‐P‐K ratio and high rates of P and K over a range of N rates. An established sod which had not receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 5 publications
4
16
0
Order By: Relevance
“…Data are presented by harvest for the 2004 growing season because DM yields were not affected in 2002 or 2003 by supplemental inorganic P fertilizer (Table 3). The optimal tissue‐P concentration for Coastal bermudagrass was 2.4 g kg −1 (Day and Parker, 1985; Kelling and Matocha, 1990) and a field study by Brink et al (2004) reported tissue‐P concentration ranging from 1.5 to 2.3 g kg −1 , which is similar to values reported in this study. In 2002 and 2003, average tissue‐P ranged from 1.8 g kg −1 to 2.8 g kg −1 in the compost treatments receiving supplemental inorganic P (data not shown).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Data are presented by harvest for the 2004 growing season because DM yields were not affected in 2002 or 2003 by supplemental inorganic P fertilizer (Table 3). The optimal tissue‐P concentration for Coastal bermudagrass was 2.4 g kg −1 (Day and Parker, 1985; Kelling and Matocha, 1990) and a field study by Brink et al (2004) reported tissue‐P concentration ranging from 1.5 to 2.3 g kg −1 , which is similar to values reported in this study. In 2002 and 2003, average tissue‐P ranged from 1.8 g kg −1 to 2.8 g kg −1 in the compost treatments receiving supplemental inorganic P (data not shown).…”
Section: Resultssupporting
confidence: 86%
“…In 2004, the third season after application, all C2, C3, and M treatments had greater tissue‐P concentrations compared with UC for all four harvests (Table 6). Compost and manure treatments receiving supplemental inorganic N had lower tissue‐P concentrations than plots not receiving supplemental N. This is attributed to greater DM and consequent nutrient removal from plots receiving supplemental inorganic N. In 2004, average tissue‐P concentrations fell to 2.0 g kg −1 in the C2 and M treatments in the third and fourth harvests, which is below the critical level of 2.4 g kg −1 (Day and Parker, 1985) and explains why supplemental inorganic P increased Coastal bermudagrass DM yields in the third season following application of the low rate of compost. Supplemental inorganic P did not affect tissue‐P concentration in the C3 treatment, indicating that higher rates of compost can provide sufficient P for up to three growing seasons and supports the observed DM yield data.…”
Section: Resultsmentioning
confidence: 98%
“…Year × treatment and harvest date × treatment interactions were signifi cant for P concentrations, so means are reported by year and harvest. The optimal tissue-P concentration for Coastal bermudagrass growth is 2.4 g kg -1 (Day and Parker, 1985;Kelling and Matocha, 1990), and a fi eld study by Brink et al (2004) reported tissue-P concentrations ranging from 1.5 to 2.3 g kg -1 , which is similar to the 1.3 to 3.2 g kg -1 range reported in this study. In 2003, earlyseason (H1) P concentrations (Table 4) were low compared with potential 3.2 g P kg -1 Coastal bermudagrass herbage reported elsewhere in the literature (Pierzynski and Logan, 1993).…”
Section: Phosphorus Concentrations and Yieldssupporting
confidence: 85%
“…The optimal tissue-P concentration for Coastal bermudagrass growth is 2.4 g kg -1 (Day and Parker, 1985;Kelling and Matocha, 1990), and a fi eld study by Brink et al (2004) reported tissue-P concentrations ranging from 1.5 to 2.3 g kg -1 , which is similar to the 1.3 to 3.2 g kg -1 range reported in this study. The optimal tissue-P concentration for Coastal bermudagrass growth is 2.4 g kg -1 (Day and Parker, 1985;Kelling and Matocha, 1990), and a fi eld study by Brink et al (2004) reported tissue-P concentrations ranging from 1.5 to 2.3 g kg -1 , which is similar to the 1.3 to 3.2 g kg -1 range reported in this study.…”
Section: Phosphorus Concentrations and Yieldssupporting
confidence: 83%
“…Coastal Plain soils of the southern United States are usually sandy, acidic, low in organic matter, and have a low buffering capacity. Nitrogen, P, and K are often the major nutrients limiting forage production on these soils (Wilkinson and Langdale, 1974; Day and Parker, 1985). Liming is necessary to maintain an adequate pH for production of improved forages, particularly in pastures receiving commercial N fertilizer (Cripps et al, 1988; Haby et al, 1999).…”
mentioning
confidence: 99%